Comparison of transverse island flap onlay and tubularized incised-plate urethroplasties for primary proximal hypospadias: a systematic review and meta-analysis. - Dongdong Xiao; Xin Nie; Wenyue Wang; Juan Zhou; Ming Zhang; Zhe Zhou; Yang Zhao; Meng Gu; Zhong Wang; Mujun Lu (PLoS ONE)
Purpose This meta-analysis was conducted to compare postoperative outcomes between transverse island flap (TVIF) onlay and tubularized incised-plate (TIP) urethroplasties for primary proximal hypospadias. Materials and methods A comprehensive literature search updated to 21st May 2014 was carried out for relevant studies. After literature identification and data extraction, odds ratio (OR) with 95% confidential interval (CI) was calculated to compare postoperative complication rate between TVIF onlay and TIP. Meta-regression and subgroup analyses were applied to find potential affective factors. Results A total of 6 studies including 309 patients receiving TVIF onlay and 262 individuals subjected to TIP met inclusion criteria. The synthetic data suggested that TVIF onlay and TIP were comparable in terms of total complication rate (OR 0.85, 95% CI 0.56-1.30, p = 0.461), fistula (OR 0.68, 95% CI 0.38-1.21, p = 0.194), recurrent curvature (OR 1.16, 95% CI 0.43-3.12, p = 0.766), dehiscence (OR 0.95, 95% CI 0.33-2.74, p = 0.920), diverticulum (OR 1.90, 95% CI 0.53-6.78, p = 0.321), meatal stenosis (OR 0.74, 95% CI 0.20-2.77, p = 0.651) and urethral stricture (OR 1.49, 95% CI 0.41-5.50, p = 0.545), without significant heterogeneity for each comparison group. Meta-regression and subgroup analyses revealed no significant findings. One-way sensitivity analysis indicated that the results were stable. No publication bias was detected using both funnel plot and Egger's test. Also, there were no obvious differences observed in cosmetic and functional outcomes. Conclusions This meta-analysis suggests that TVIF onlay and TIP urethroplasties are clinically equivalent. Given the inherent limitations of included studies, this conclusion should be interpreted with caution and wait to be confirmed by more well-designed randomized controlled trials with high quality in the future.